Историко-социологическое источниковедение: задачи и методы исследования - Городяненко, В. (Социология: теория, методы, маркетинг, 2000)
Theoretical and methodological aspects of historico-sociological source knowledge are stipulated by the specificity of the history of sociology as a concrete branch of science. The tasks of source knowledge in this scientific branch include: developing the general concept of its subject and structure, delineating its methodology within the frame of social science instrumentation, analyzing a historico-sociological source as a social phenomenon and the vehicle of historical information, source of classification and systematization. There are presented such methods as those of “external” and “internal” source criticism, as well as the biographical method in its application to sources knowledge.